Inovasi dalam Evaluasi Kebijakan Publik - Muhammad Adib Farhan; Dimas Febrianto; Eka Widiarti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Innovation in public policy evaluation has become an important issue in improving policy effectiveness and efficiency. This study aims to analyze the role of innovation in public policy evaluation, identify effective innovative approaches, and explore the challenges and opportunities of their implementation in Indonesia. The method used is a literature review, which includes a critical analysis of various previous studies. The results show that innovations, such as the use of digital technology and participatory evaluation models, can improve the quality of policy evaluation. Technology enables faster and more accurate data collection, while public participation provides richer perspectives. However, challenges such as limited data availability, low transparency, and minimal public participation remain major obstacles. This study also reviews best practices from other countries as references for the local context. These findings provide recommendations for policymakers to adopt more modern and inclusive approaches to policy evaluation, in line with the principles of good governance. Thus, public policy evaluation is expected to become a more adaptive and relevant instrument in supporting evidence-based decision-making.